Natural Evolution of Incomplete Reperfusion in Patients Following Endovascular Therapy After Ischemic Stroke - Mujanovic, Adnan; Windecker, Daniel; Cimflova, Petra; Meinel, Thomas R; Seiffge, David J; Auer, Elias; Boulouis, Grégoire; Arnold, Marcel; Serrallach, Bettina L; Rohner, Roman; Janot, Kevin; Dobrocky, Tomas; et al. (Stroke, 2025)
BACKGROUND: A third of endovascularly treated patients with stroke experience incomplete reperfusion (expanded Thrombolysis in Cerebral Infarction [eTICI] <3), and the natural evolution of this incomplete reperfusion remains unknown. We systematically reviewed the literature and performed a meta-analysis on the natural evolution of incomplete reperfusion after endovascular therapy. METHODS: A systematic review of MEDLINE, Embase, and PubMed up until March 1, 2024, using a predefined strategy. Only full-text English-written articles reporting rates of either favorable (ie, delayed reperfusion (DR) or no new infarct) or unfavorable progression (ie, persistent perfusion deficit or new infarct) of incompletely reperfused tissue were included. The primary outcome was the rate of DR and its association with functional independence (modified Rankin Scale score, 0-2) at 90 days postintervention. Pooled odds ratios with 95% CIs were calculated using a random-effects model. RESULTS: Six studies involving 950 patients (50.7% female; median age, 71 years; interquartile range, 60-79) were included. Four studies assessed the evolution of incomplete reperfusion on magnetic resonance imaging perfusion imaging, while 2 studies used diffusion-weighted imaging and noncontrast computed tomography imaging, where new infarct was used to denote unfavorable progression. Five studies defined incomplete reperfusion as eTICI 2b50 or 2c. DR occurred in 41% (interquartile range, 33%-51%) of cases 24 hours postintervention. Achieving DR was associated with a higher likelihood of functional independence at 90 days (odds ratio, 2.5 [95% CI, 1.9-3.4]). CONCLUSIONS: Nearly half of eTICI <3 patients achieve DR, leading to favorable clinical outcomes. This subgroup may derive limited or potentially harmful effects from pursuing additional reperfusion strategies (eg, intra-arterial lytics or secondary thrombectomy). Accurately predicting the evolution of incomplete reperfusion could optimize patient selection for adjunctive reperfusion strategies at the end of an intervention. REGISTRATION: URL: https://www.clinicaltrials.gov; Unique identifiers: NCT05499832.
Keywords: trombolytická terapie; výsledek terapie; ischemická cévní mozková příhoda; Male; Endovascular Procedures; reperfuze; perfusion imaging; Ischemic Stroke; stroke; endovaskulární výkony; endovascular procedures; Aged; mužské pohlaví; senioři; Thrombolytic Therapy; Treatment Outcome; Reperfusion; lidé; functional status; ženské pohlaví; Humans; reperfusion; Female; lidé středního věku; Middle Aged